Factors influencing the implementation of agroecological practices: Lessons drawn from the Aba-Garima watershed, Ethiopia - Mekuria, Wolde; Dessalegn, Mengistu; Amare, Dagninet; Belay, Beyene; Getnet, Banchiamlak; Girma, Gonche; Tegegne, Desalegn (Frontiers in Environmental Science, 2022)
The challenges to agroecological transitions are not the same for all farmers and implementation in a different location could yield completely different results. Thus, this study was conducted in Aba-Garima watershed, Ethiopia to characterize the structure and activities of the farming households and farming practices and assess factors influencing the implementation and sustainability of agroecological practices. Data were collected from 218 households, 16 key informants, and 12 focus group discussions. The Multivariate Probit model and descriptive statistics were employed to analyze factors influencing farmers’ choice of different agroecological practices and characterize the farming households, respectively. The qualitative data analysis was processed through topic coding and building categories, themes, and patterns of relationships. Farmers realize the importance of both farm and landscape level agroecological practices to enhance income earning capacity, achieve food security and protect the environment. However, most of the agroecological practices are very difficult to start using for various constraining factors including limited access to water, and shortages of money, land and labor. The results suggest that depending on different socio-economic characteristics of farming households, agroecological practices that appear common practices can be very difficult to employ for some farmers, while it could be possible for other farmers. This, in turn suggest that the constraining factors are differently associated with different practices, involving the perspectives of different socio-economic groups. The paper discussed the existing agroecological practices, the perspectives of the different socio-economic groups on the practices and factors influencing the implementation as well as conditions that can facilitate the wider adoption of agroecological practices in the study area.